2020
DOI: 10.31234/osf.io/5pa9r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Similarity judgment within and across categories: A comprehensive model comparison

Abstract: Similarity is one of the most important relations humans perceive, arguably subserving category learning and categorization, generalization and discrimination, judgment and decision making, and other cognitive functions. Researchers have proposed a wide range of representations and processes that could be at play in similarity judgment, yet have not comprehensively compared the power of these representations and processes for predicting similarity within and across different semantic categories. We performed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Our final application showed that BERT was able to predict patterns in similarity judgment that are problematic for existing distributed semantics models. These patterns involve asymmetry in similarity judgment (Whitten et al, 1979), the distinction between association and similarity (Hill et al, 2015), and the measurement of similarity within (rather than across) categories (Richie & Bhatia, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our final application showed that BERT was able to predict patterns in similarity judgment that are problematic for existing distributed semantics models. These patterns involve asymmetry in similarity judgment (Whitten et al, 1979), the distinction between association and similarity (Hill et al, 2015), and the measurement of similarity within (rather than across) categories (Richie & Bhatia, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Word vector representations learned through these methods have been enormously successful in psychological applications (for reviews see Bhatia et al, 2019;Günther et al, 2019;Jones et al, 2015;Lenci, 2018;Mandera et al, 2017). For example, cosine similarity between word vectors correlates with Likert-scale judgments of words' similarity and relatedness (Richie & Bhatia, 2020;Hill et al, 2015), strength of semantic priming in, e.g., the lexical decision task, as measured by reaction times (Jones et al, 2006;Mandera et al, 2017), and even with probability of recall given a cue in free association, or given an earlier recalled item in list and category recall (although there are often better ways to use word vectors for such tasks rather than simply computing cosine; see Nematzadeh et al, 2017 andJones et al, 2018). Semantic judgments about words (e.g.…”
Section: Distributed Semanticsmentioning
confidence: 99%
See 2 more Smart Citations
“…One popular DS model is word2vec, which projects each word of its input into a common, lower-dimensional space [61,62]. Words that are closer together in this space are more semantically similar [63,64]. One common way to measure this distance is using cosine similarity, or the cosine of the angle between the vector representations of two words.…”
Section: Study 2: Controlling For Word Sense Using Cosine Similaritymentioning
confidence: 99%